The Correlation Between Classroom Seating Position and Speaking Ability of a 9th Grader - Presti, Happy; Rasyid, Tri Rositasari; Hartati, Sri (CV. Doki Course and Training, 2024)
English is regarded as an international language, one of the most widely used languages in all fields. In Indonesia, the government recognized that English proficiency had an impact on global development not only for education but also for career purposes. English is useful in a variety of fields. The limitation of the study was only focused on “The Correlation between Classroom Seating Position and Speaking Ability of 9th Grade Students of SMP Muhammadiyah 4 Palembang”. The objectives of this study were found out whether or not there is a significant correlation between Classroom Seating Position and Speaking Ability. This study used quantitative research design with correlational approach. The researchers used a purposive sampling, total of population were 172 students and the total of sample were 27 students. The data were collected by two instruments, (1) through ready-made questionnaires, (2) speaking test was analysed by using SPSS 26. The result of this study was that there was a correlation between two variables, with r-obtained (0.797) was higher than r-table (0.388). The conclusion of this study was that the alternative hypotheses (Ha) was accepted and the null hypotheses (H0) was rejected. Then there was a high correlation between the two variables.